Nature and causes of injury in amateur rugby union players: Malaysian rugby super league 2016 / Ahmad Zainal Rushd Ahmad Rosdi - Ahmad Rosdi, Ahmad Zainal Rushd (Faculty of Sport Science and Recreation, 2016)
The purpose of this study was to analyze the types and mechanisms of injuries occurred during the 2016 Rugby Super League on the players and does the playing positions affect the injuries possessed by the players. Furthermore, the purpose of this study to find out are there any association or relationship between player's position and types, location and causes of injury. A total of two hundred and fifty two (n=252) participated in this study and the subject selection were based on random purposive sampling. The study only account for players who suffer injuries, where there were one hundred and thirty seven (n=137). This study calculated the data based on the number of cases. Location of injury (n= 237), Type of injury (n= 219) and Causes of injury (n= 255). Results showed 3 different results where there were no significant association (p= .162) in player's position and the locations of injury, no significant association (p= .949) in player's position and the types of injury and there is no significant association (p= .861) in player's position with the causes of injury. As a conclusion for this study, the outcome could be useful for future references and could aid the coaches on safer methods of training and it can also provide guidelines for the coaches to prepare an injury prevention program.